Synthesis, Magnetic Properties, and Catalytic Properties of a Nickel(II)-Dependent Biomimetic of Metallohydrolases - Horn Jr., Adolfo; Englert, Daniel; Roberts, Asha E.; Comba, Peter; Schenk, Gerhard; Krenske, Elizabeth H.; Gahan, Lawrence R. (Frontiers in Chemistry, 2018)
A dinickel(II) complex of the ligand 1,3-bis(bis(pyridin-2-ylmethyl)amino)propan-2-ol (HL1) has been prepared and characterized to generate a functional model for nickel(II) phosphoesterase enzymes. The complex, [Ni2(L1)(μ-OAc)(H2O)2](ClO4)2·H2O, was characterized by microanalysis, X-ray crystallography, UV-visible, and IR absorption spectroscopy and solid state magnetic susceptibility measurements. Susceptibility studies show that the complex is antiferromagnetically coupled with the best fit parameters J = −27.4 cm−1, g = 2.29, D = 28.4 cm−1, comparable to corresponding values measured for the analogous dicobalt(II) complex [Co2(L1)(μ-OAc)](ClO4)2·0.5 H2O (J = −14.9 cm−1 and g = 2.16). Catalytic measurements with the diNi(II) complex using the substrate bis(2,4-dinitrophenyl)phosphate (BDNPP) demonstrated activity toward hydrolysis of the phosphoester substrate with Km 10 mM, and kcat 0.025 s−1. The combination of structural and catalytic studies suggests that the likely mechanism involves a nucleophilic attack on the substrate by a terminal nucleophilic hydroxido moiety.